2018
DOI: 10.1186/s13058-018-1067-y
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab treatment is associated with the absence of circulating tumor cells in patients with breast cancer

Abstract: BackgroundThe presence of circulating tumor cells (CTCs) in patients with breast cancer correlates to a bad prognosis. Yet, CTCs are detectable in only a minority of patients with progressive breast cancer, and factors that influence the abundance of CTCs remain elusive.MethodsWe conducted CTC isolation and enumeration in a selected group of 73 consecutive patients characterized by progressive invasive breast cancer, high tumor load and treatment discontinuation at the time of CTC isolation. CTCs were quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
0
21
3
Order By: Relevance
“…At baseline, clusters were isolated in 50% of our patient cohort. This is slightly higher than recently reported by Vetter et al, who found 35% of their cohort had clusters present prior to treatment [26], using the Parsortix microfluidic device. Studies using the CellSearch™ system report cluster rates around 20% [27].…”
Section: Discussioncontrasting
confidence: 64%
“…At baseline, clusters were isolated in 50% of our patient cohort. This is slightly higher than recently reported by Vetter et al, who found 35% of their cohort had clusters present prior to treatment [26], using the Parsortix microfluidic device. Studies using the CellSearch™ system report cluster rates around 20% [27].…”
Section: Discussioncontrasting
confidence: 64%
“…Otherwise, Vetter and colleagues 42 recently reported in a small size sample (n = 20) that some breast cancer patients turned negative during denosumab treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Main methodological differences between the two studies prevent a direct comparison of the data, namely the criteria for defining a cell as CTC -EpCAM + CD45-in Vetter study vs. EpCAM + CK + DAPI + CD45-in our study-, and the procedure for CTC enumeration -manual vs. automated procedure, respectively. Moreover, Vetter www.nature.com/scientificreports www.nature.com/scientificreports/ and colleagues 42 did not describe the time-line schedule of blood draws subsequent the baseline one, hence we cannot compare time-matched CTC enumeration.…”
Section: Discussionmentioning
confidence: 99%
“…It would be beneficial to accumulate more knowledge in regard to the shedding process; does it occur constantly or in waves and what stimuli trigger it? For example, it was recently demonstrated that CTCs' presence correlates with low red blood cell count and that the treatment with the monoclonal antibody denosumab is associated with the absence of CTCs [22].…”
Section: Factors Affecting the Number Of Circulating Tumor Cells (Ctcmentioning
confidence: 99%